PERFORMANCE OF HYBRID PIGEONPEA ( PERFORMANCE OF HYBRID PIGEONPEA (CAJANUS CAJAN L.) AS INFLUENCED BY NUTRIENT AND LIME LEVELS UNDER RAINFED CONDITION OF JHARKHAND - SINGH, S. K; PURAN, A. N; KARMAKAR, S (The Bioscan, 2016)
A field experiment was conducted during kharif season of 2009-10 at Birsa Agricultural University, Ranchi, to find out the effect of varying levels of nutrient and lime application on the performance hybrid pigeonpea. The experiment was laid out in randomized block design (factorial) with three replication keeping three nutrient levels (100% RDF, 150% RDF and 200% RDF) and three lime levels (control, 200 and 400 kg/ha). Application of 150% recommended dose of fertilizer (30:60:30:30 kg NPKS/ha) gave significantly higher plant height, leaf area index, number of primary branches/plant, number of secondary branches/plant, number of pods/plant, number of seeds/pod, 100 seed weight, grain yield (16.63 q/ha) and stover yield (49.99 q/ha) which ultimately resulted in significantly higher net return (Rs. 34573/ha) hybrid pigeonpea. However, it was statistically at par with 200% RDF (40:80:40:40 kg NPKS). The nutrient level failed to cause significant variation in harvest index and B: C ratio. Application of lime upto 200 kg/ha significantly improved the plant height, leaf area index, number of primary and secondary branches/plant, number of nodules/plant, dry weight of nodules/plant, number of pods/plant, number of seed/pods, 100 seed weight, grain yield (17.40 q/ha), stover yield (51.62 q/ha), net return (Rs. 51242/ha) and B:C Ratio (2.53) of hybrid pigeonpea Economics Hybrid pigeonpea Lime Nodulation Nutrient levels